Observation of the Doubly Charmed Baryon Ξ++cc; Physical Review Letters; Vol. 119, iss. 4 - Aaij R. Roel; Adeva B. Bernardo; Adinolfi M.; Ajaltouni Z. J. Zeina; Akar S. Simon; Vagner A. R. Aleksandr Rudolfovich (2017, 2017)
Title screen